2020
DOI: 10.1002/star.201900220
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Mechanical, Functional, and Thermal Characterization of Chitosan: Maltodextrin Blends Edible Oral Film Incorporated with Aqueous Clove Extract

Abstract: The oral route is the most effective and fast route for the administration of therapeutic and antioxidant agents at low cost with high patient compliance. In this work, natural clove extract is used as an anti‐oxidative agent in developing chitosan‐maltodextrin based edible oral thin films (OTFs). The antioxidant enriched edible OTFs are evaluated for enhanced oral bioavailability and functionality. The different formulations are as follows; F1 (100% maltodextrin), F2 (25:75%, chitosan: maltodextrin), F3 (50:5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…It was found that Tg decreased with the incorporation of additives due to the decreased crystallinity of the composite films. [30][31][32] Tg is also related to the molecular weight of the compositions of materials. [33] The molecular weight of TFP reported by other researchers ranged from 2.35 × 10 6 to 3.43 × 10 6 g mol −1 , which was smaller than that of corn starch (form 5.51 × 10 7 to 1.4 × 10 8 g mol −1 ).…”
Section: Glass Transition Temperature (Tg)mentioning
confidence: 99%
“…It was found that Tg decreased with the incorporation of additives due to the decreased crystallinity of the composite films. [30][31][32] Tg is also related to the molecular weight of the compositions of materials. [33] The molecular weight of TFP reported by other researchers ranged from 2.35 × 10 6 to 3.43 × 10 6 g mol −1 , which was smaller than that of corn starch (form 5.51 × 10 7 to 1.4 × 10 8 g mol −1 ).…”
Section: Glass Transition Temperature (Tg)mentioning
confidence: 99%
“…The light source of transmittance was 600-4000 cm −1 . [32,33] The spectra obtained were used to determine the functional groups between almond and guar gum and effect of Microfludization (10 000 and 15 000 psi) on developed almond gum composite edible films. The FTIR spectra depict mean value of 23 conservative scans.…”
Section: Fourier-transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 99%